Penerapan life cycle assessment pada proses produksi di PT. Royal Coconut Gorontalo - Bayu, Muh Aditya Utomo; Rasyid, Abdul; Uloli, Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT Royal Coconut Gorontalo is a company that processes coconut into coconut flour, coconut oil and meal products. This company has experienced cases of environmental pollution caused by less than optimal waste treatment. The purpose of this study is to determine the magnitude of the environmental impact of the production process in the company. One of the efforts to determine the magnitude of environmental impacts caused by the production process is using the Life Cycle Assessment (LCA) method. The results of this method can determine the critical points that cause environmental impacts so that several alternative recommendations for improvement are obtained. Determination of the best alternative recommendations using the Analytical Network Process (ANP) method. ANP is one method to measure the priority scale in making a decision. The results of environmental impacts using the LCA approach with eco-indicator 99 method are respiratory inorganics with a value of 8.2382 kPt, while the results of the ANP method concluded that the alternative use of briquettes as boiler fuel and environmental impact criteria as the top priority in environmental improvement.